Performance of Embankments on Soft Ground: A1033 Hedon Road Improvement Scheme, UK - O'Kelly, Brendan (My University, 2008)
This paper presents the response of the ground foundation during the construction of the approach embankments to a new flyover at Salt End junction, A1033 Hedon Road Improvement Scheme, UK. The site area was underlain by about 8.0 m depth of soft alluvial deposits and the design specification required, amongst other factors, 100% consolidation of the alluvium under the higher embankments before the construction of the pavement layers could commence. The design solution incorporated ground improvement (prefabricated vertical drains and temporary surcharge) and a basal reinforcement layer in the transition zones next to the bridge abutments. An array of ground instrumentation monitored in real time the pore water pres-sure and deformation responses of the different strata comprising the ground foundation. The actual values of the primary consolidation parameters were determined from a back analysis of the settlement data.
Invited presentation at the First International Conference on Transportation Geotechnics
PRESENTED
Nottingham, UK
Keywords: Geotechnics